Agricultural oasis at the southern puna: Ancient water management in Antofagasta de la Sierra (Argentina) - Grana, Lorena Giselle (2020)
The objective of the presentation is to show how a number of simple hydrological technics enabled the irrigation of a vast area of Antofagasta de la Sierra (Puna-Argentina) during the Prehispanic period. Through a combination of multiscale methods (including satellite imagery analysis, ground-proofing survey, excavation, and diatom analysis of the features), we revealed five different irrigation networks with distinct designs and different scales of use. This allows us to figure out the complexity of knowledge about ancient water management, better understand societies´ capacities to adapt to desert conditions, and learn about the creation of agricultural oases.